Distribution of anisakid nematodes parasitizing rajiform skates under commercial exploitation in the Southwestern Atlantic - Irigoitia, Manuel Marcial (2018)
In order to evaluate the infestation by anisakids present in elasmobranchs and their distribution in the Argentine Sea, this study was carried at a regional scale with the following aims: 1) to identify those anisakid species present in skates under exploitation; 2) to characterize quantitatively these infestations and 3) to determine those factors driving the variability in parasite burdens across skate species. A total of 351 skates, belonging to 3 species (218 Sympterygia bonapartii, 86 Zearaja chilensis and 47 Atlantoraja castelnaui) and from different localities of the Argentine Sea were examined for anisakids. Parasites were found in the stomach wall at high prevalence in some samples. Based on morphology and mtDNA cox2 sequences analyses (from 24 larval worms), specimens were identified as Anisakis berlandi, A. pegreffii and Pseudoterranova cattani; the last two known as potentially pathogenic for humans. Differential distribution patterns were observed across parasite and hosts species. In general, fish caught in southern and deeper waters exhibited higher loads of Anisakis spp., whereas infestation levels by P. cattani increase in larger skates. Taking into account that the mere presence of worms or their antigens in fish meat can provoke allergic responses, information on distribution of parasites and their variability is essential for the implementation of food safety practices.